2008
DOI: 10.1016/j.ejheart.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of a short deceleration time in symptomatic congestive heart failure☆

Abstract: Aims: A restrictive transmitral filling (RF) pattern predicts increased mortality in heart failure (HF) with reduced left ventricular (LV) systolic function. We performed a combined evaluation of LV function and RF for prognosis in patients with HF with and without systolic dysfunction. Methods and results: Doppler echocardiography was performed in 972 patients with symptomatic HF. RF was considered present when deceleration time (DT) was ≤140 ms and non-RF when N 140 ms. A DT N 240 ms was defined as delayed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…As previously shown [7], having a restrictive filling pattern was associated with an increased risk of mortality, but importantly this relative risk was substantially higher among patients with hypertension than among patients without hypertension (Figure 3a). Further, the transmitral filling pattern was shown to substantially influence the outcomes associated with hypertension; p for interaction <0.001; Figure 3b.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…As previously shown [7], having a restrictive filling pattern was associated with an increased risk of mortality, but importantly this relative risk was substantially higher among patients with hypertension than among patients without hypertension (Figure 3a). Further, the transmitral filling pattern was shown to substantially influence the outcomes associated with hypertension; p for interaction <0.001; Figure 3b.…”
Section: Resultssupporting
confidence: 77%
“…Measurements of transmitral filling pattern (i.e., peak flow velocity and deceleration time in early diastole [E wave] and peak flow velocity in atrial contraction [A wave]) were obtained as averages of 5 consecutive cardiac cycles for patients in sinus rhythm and 10 cardiac cycles for patients in atrial fibrillation. A restrictive left ventricular filling pattern was considered present if transmitral deceleration time was below or equal to 140 ms [7]. Atrial fibrillation was no exclusion criteria, because a short deceleration time has shown to be of similar prognostic importance in patients with and without atrial fibrillation [8-10].…”
Section: Methodsmentioning
confidence: 99%
“…However, relying on a univariate predictor such as LVEF to predict the prognosis is not sufficient, and patients with HFrEF and diastolic dysfunction have a lower survival rate. Both a deceleration time ≤ 140 ms and early to late flow velocity of mitral inflow > 1 mean have been shown to be powerful independent predictors of mortality according to studies which evaluated mitral inflow patterns by Doppler echocardiography [34] [35]. In addition, Temporelli et al reported that after optimal medical treatment, the patients’ response to medication with reversal of the restrictive pattern at 6 months resulted in a lower cardiac mortality rate and fewer events requiring hospitalization than those with persistence of the restrictive pattern [36].…”
Section: Discussionmentioning
confidence: 99%
“…The trial design and results have been described in detail previously [20,21]. Briefly, from 2001 to 2002, 3954 consecutive patients admitted with congestive HF were screened in 43 hospitals in Scandinavia, primarily Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac cycles with fusion of early and late velocities or with nonlinear deceleration slope were excluded. RF was considered present when deceleration time was ≤140 ms [21]. …”
Section: Methodsmentioning
confidence: 99%